Assessment of Ground Water Quality for making Ready Mix Concrete Production. - M , Tholkapiyan; S , Prasanna venkatesh (International Journal of Psychosocial Rehabilitation, 2020)
This paper deals with the quality of water used for making cement concrete by Ready-Mix Concrete (RMC) producers in Chennai. Water samples are collected from three different RMC plants located in Chennai, and the water samples are assessed for chemical properties in accordance with relevant Indian standards, and the analyzed method of their growth is collected. The limits of chemical properties as per Indian standards are presented, and results are discussed for the suitability of water samples for the production of Ready-Mix Concrete for the construction industry. The utilization of polluted water for solid blending is seen as too great for quality advancement at early ages and a decrease in long-haul quality.